USING WEB CORPORA FOR LINGUISTIC RESEARCH (Ustozlar uchun, 2025)
Web corpora—large collections of linguistic data gathered from the internet—have become essential tools in modern linguistic research. This article examines how web-derived corpora contribute to the study of vocabulary, grammar, discourse, and language variation. It analyzes the methodological advantages and limitations of using online data, highlights examples from widely used corpora such as the Corpus of Contemporary American English (COCA), the iWeb Corpus, and the TenTen corpora, and discusses how researchers employ web-harvested data for quantitative and qualitative analysis. The article argues that web corpora, despite their challenges, provide unparalleled access to vast, up-to-date linguistic data and therefore have transformed empirical language study.